Fintech P2P Lending dalam Pandangan Islam - Yolanda Salsabila; Juliana Putri (Equivalent : Journal of Economic, Accounting and Management, 2025)
Abstract : Sharia peer-to-peer (P2P) lending is a fintech innovation that connects funders and borrowers through digital platforms while applying sharia principles such as the prohibition of usury (riba), uncertainty (gharar), and the use of sharia contracts (mudharabah, musyarakah, qardh, wakalah). Sharia P2P lending plays a crucial role in expanding access to financing for MSMEs and communities not reached by conventional banking services in Indonesia. However, its implementation still faces challenges, including unspecific regulations, low sharia financial literacy, limited human resources, as well as suboptimal consumer protection and sharia supervision. With strengthened regulations, education, and sharia-based governance, sharia P2P lending is expected to continue growing and make a significant contribution to sharia financial inclusion and national economic development. Abstrak : Peer-to-peer (P2P) lending syariah merupakan inovasi fintech yang mempertemukan pemberi dana dan peminjam melalui platform digital dengan menerapkan prinsip-prinsip syariah, seperti larangan riba, gharar, dan penggunaan akad-akad syariah (mudharabah, musyarakah, qardh, wakalah). P2P lending syariah berperan penting dalam memperluas akses pembiayaan bagi UMKM dan masyarakat yang belum terjangkau layanan perbankan konvensional di Indonesia. Namun, implementasinya masih menghadapi tantangan berupa regulasi yang belum spesifik, rendahnya literasi keuangan syariah, keterbatasan sumber daya manusia, serta perlindungan konsumen dan pengawasan syariah yang belum optimal. Dengan penguatan regulasi, edukasi, dan tata kelola berbasis syariah, P2P lending syariah diharapkan dapat terus berkembang dan memberikan kontribusi signifikan terhadap inklusi keuangan syariah dan pertumbuhan ekonomi nasional.